Epidemiology Characteristics of Streptococcus pneumoniae From Children With Pneumonia in Shanghai: A Retrospective Study - Zhao, Wantong; Pan, Fen; Wang, Bingjie; Wang, Chun; Sun, Yan; Zhang, Tiandong; Shi, Yingying; Zhang, Hong (Frontiers in Cellular and Infection Microbiology, 2019)
Background:Streptococcus pneumoniae is the most common pathogen causing death in children under 5 years old. This retrospective surveillance aimed to analyze serotype distribution, drug resistance, virulence factors, and molecular characteristics of pneumonia isolates from children in Shanghai, China. Methods: A total of 287 clinical pneumococcal isolates were collected from January to December in 2018 and were divided into community-acquired pneumonia (CAP) and healthcare-associated pneumonia (HAP) two groups according to where someone contracts the infection. All isolates were serotyped by multiplex sequential PCR and antimicrobial susceptibility testing was performed using E-test or disk diffusion method. The molecular epidemiology was analyzed using multilocus sequence typing and seven housekeeping genes were sequenced to identified the sequence types (STs). In addition, we investigated the presence of virulence genes via PCR. Results: The most common serotypes were 19F, 6A, 19A, 23F, 14, and 6B, and the coverage rates of the 7-, 10- and 13-valent pneumococcal conjugate vaccines were 58.9, 58.9, and 80.5%, respectively. More PCV13/non-PCV7 serotypes and higher rate of penicillin non-susceptible S. pneumoniae were seen in HAP. Molecular epidemiological typing showed a high level of diversity and five international antibiotic-resistant clones were found, including Taiwan19F-14, Spain23F-1, Spain6B-2, Taiwan23F-15 and Sweden15A-25. No significant difference was observed in the presence of virulence genes among the isolates obtained from CAP and HAP. All of the S. pneumoniae isolates carried lytA, ply, psaA, pavA, spxB, htrA, and clpP, and the carriage rate of nanA and piaA were 96.2 and 99.0%. Conversely, cps2A, cbpA, and pspA were present in 33.8–44.3% of the isolates. Conclusions: Serotype changes and emerging multidrug-resistant international clones were found in current study. lytA, ply, psaA, pavA, spxB, htrA, and clpP may be good protein vaccine candidates. Long-term high-quality surveillance should be conducted to assess impact and effectiveness brought by vaccines, and provide a foundation for prevention strategies and vaccine policies.